Novel bioresources for studies of Brassica oleracea: identification of a kale MYB transcription factor responsible for glucosinolate production. Issue 8 (30th July 2013) - Araki, Ryoichi; Hasumi, Akiko; Nishizawa, Osamu Ishizaki; Sasaki, Katsunori; Kuwahara, Ayuko; Sawada, Yuji; Totoki, Yasushi; Toyoda, Atsushi; Sakaki, Yoshiyuki; Li, Yimeng; Saito, Kazuki; Ogawa, Toshiya; et al.
Summary Plants belonging to the Brassicaceae family exhibit species‐specific profiles of glucosinolates (GSLs), a class of defence compounds against pathogens and insects. GSLs also exhibit various human health–promoting properties. Among them, glucoraphanin (aliphatic 4‐methylsulphinylbutyl GSL) has attracted the most attention because it hydrolyses to form a potent anticancer compound. Increased interest in developing commercial varieties of Brassicaceae crops with desirable GSL profiles has led to attempts to identify genes that are potentially valuable for controlling GSL biosynthesis. However, little attention has been focused on genes of kale (Brassica oleracea var. acephala). In this study, we established full‐length kale cDNA libraries containing 59 904 clones, which were used to generate an expressed sequence tag (EST) data set with 119 204 entries. The EST data set clarified genes related to the GSL biosynthesis pathway in kale. We specifically focused on BoMYB29, a homolog of Arabidopsis MYB29/PMG2/HAG3, not only to characterize its function but also to demonstrate its usability as a biological resource. BoMYB29 overexpression in wild‐type Arabidopsis enhanced the expression of aliphatic GSL biosynthetic genes and the accumulation of aliphatic GSLs. When expressed in the myb28myb29 mutant, which exhibited no detectable aliphatic GSLs, BoMYB29 restored the expression of biosynthetic genes and aliphatic GSL accumulation. Interestingly, the ratio of methylsulphinyl GSL content, including glucoraphanin, to that of methylthio GSLs was greatly increased, indicating the suitability of BoMYB29 as a regulator for increasing methylsulphinyl GSL content. Our results indicate that these biological resources can facilitate further identification of genes useful for modifications of GSL profiles and accumulation in kale.